Religieuze rechten voor minderheden: Een uitweg uit het multiculturele drama? - Ven, Johannes A. van der (Tijdschrift voor theologie, 2007)
Is a spirituality of hospitality sufficient for supplying relief to immigrant minorities or is a legal framework needed in which justice can be added to ‘caritas’? Is the ascription of rights, particularly religious rights, not a prerequisite? The first part of this article treats minority rights in conjunction with freedom of religion. Both are omitted from the ‘Covenant of the League of Nations’ (1919) because they were seen as collective rights and source of conflict. With the establishment of the United Nations, freedom of religion was included as individual right in the ‘Universal Declaration of Human Rights’ (1948). Nearly twinty years later, the same happened with rights for minorities in the UN ‘International Covenant on Civil and Political Rights’ (1966). Can the further development of these rights provide an answer to the multicultural drama in which our society has become entangled? The second part of the article invokes two principles to focus this question on religious rights: separation of church and state and freedom of religion. Even though they belong to the foundation of the democratic constitutional state, they are not unchallenged. Not only do they contain many problems of interpretation, secularised groups consider them superfluous. And because they incorporate numerous conflicts with other basic rights, especially the prohibition against discrimination, there are those who call for their removal from constitutions. However, it is argued, removing them would be disastrous for the minorities for whom religion is part of identity. The article then describes, against this background, several conditions for the debate on religious rights. The process of recognising rights must be consistent with developments, especially religious developments, within the minorities and the arguments for them should be couched in both religious and public parlance. The third part describes a few examples of current and possible religious rights - including the occasionally fundamental problems that they contain - relating to sections in public law, labour law, health law and the law of persons. The ascription of religious rights is contested in this last area in particular, because of the possible infringement of the equality of man and woman as in marriages, particularly in the matter of polygamy. The question is: In what is considered a weak legal pluralism, can legal forms be developed under customary law - such as the South African Polygamy Act (1998) - that can do away with these infringements? The conclusion is that the spirituality of hospitality remains offered to individual persons and small groups of immigrant minorities, but that on a collective level, a firm legal framework must also give them the religious recognition to which they also have a right.